Proteomics Research on Gastric Intraepithelial Neoplasia - GUAN Xiaoying; WANG Furong (Zhongliu Fangzhi Yanjiu, 2018)
Objective To investigate the expression of differential proteins in the typical process of gastric intraepithelial neoplasia including normal gastric antrum mucosa, reactive hyperplasia, low-grade intraepithelial neoplasia, high-grade intraepithelial neoplasia and intramucosal carcinoma. Methods We enrolled 150 specimens of different stages of gastric tissues, including normal gastric antrum mucosa, reactive hyperplasia, low-grade intraepithelial neoplasia, high-grade intraepithelial neoplasia and early gastric cancer(each n=30). The expression profiles of total proteins were detected by label-free quantification technology integrated with liquid chromatography-tandem mass spectrometry (LC-MS/MS). Potential biological function of differential proteins was analyzed. Results We screened out eight differential proteins. Compared with normal gastric antrum mucosa, during the process of gastric intraepithelial neoplasia including low-grade intraepithelial neoplasia, high-grade intraepithelial neoplasia and intramucosal carcinoma, the expression of five proteins LAMN1, ERGIC1, UQCRFS1, UQCRH, CISD1 gradually decreased, and three proteins with increasing expressions were HMGB1, DNA-PKcs, 14-3-3. Conclusion There are many proteins expressed differently in different stages of gastric cancer. They might be expected to be novel early diagnostic and targeted therapeutic biomarkers.